A Microbiological Comparison of Poultry Products Obtained from Farmers' Markets and Supermarkets in Pennsylvania. Issue 3 (3rd June 2013) - Scheinberg, Joshua; Doores, Stephanie; Cutter, Catherine N.
Abstract The popularity of farmers' markets continues to rise in the U.S.A. Raw poultry products sold at farmers' markets are of particular concern due to the United States Department of Agriculture inspection exemption status afforded to many poultry vendors. Whole chicken from farmers' markets and supermarkets in Pennsylvania were evaluated for the prevalence of Campylobacter spp. and Salmonella spp. and demonstrated that 28% (28/100) and 90% (90/100) of chicken from farmers' markets, 20% (10/50) and 28% (14/50) of conventionally processed organic, and 8.0% (4/50) and 52% (26/50) of nonorganic chicken, were positive for Salmonella spp. and Campylobacter spp., respectively. Additionally, among the 90% of Campylobacter spp.‐positive farmers' market poultry, 67% of rinses were enumerable, with a mean count of 1.6 log10 cfu/mL. The results from this study demonstrate the need to develop food safety training for poultry vendors at farmers' markets in order to improve the safety of these products for public consumption. Practical Applications The popularity of farmers' markets is increasing throughout the U.S.A. Vendors are selling numerous food products, including raw chicken, which is known to harbor Campylobacter spp. and Salmonella spp. As such, their control continues to be a priority during commercial chicken processing. However, no study has evaluated the presence of these pathogens in raw chicken sold at farmers' markets. The data collected in this study demonstrated that of the raw, whole chicken carcasses sampled from farmers' markets in Pennsylvania, 90 and 28% were contaminated with Campylobacter spp. and Salmonella spp., respectively. These results suggest that vendors could greatly benefit from food safety training and education to address antimicrobial interventions during processing. This study also demonstrates the rationale for further research into the safety of foods sold at farmers' markets. This information may also be useful to local and state regulatory officials responsible for food safety.